Sex-specific associations between exclusive breastfeeding and postpartum depression in Chinese women - Liping Meng; Mingyang Wu; Jialin Situ; Yinging Gu; Songxu Peng (BMC Pregnancy and Childbirth)
Abstract Background Studies on the association of exclusive breastfeeding and postpartum depression (PPD) are inconsistent and no prior study has investigated whether this association was influenced by other factors. This study aimed to investigate the correlation between exclusive breastfeeding and PPD in Chinese population, as well as to determine whether other factors influence this association. Methods A cross-sectional survey was carried out on 7685 postpartum women from a hospital of Shenzhen, China, utilizing the Edinburgh Postnatal Depression Scale (EPDS) to evaluate PPD. Results A total of 7685 women were included this study, of whom 4549 (59.2%) performed exclusive breastfeeding, and 3136 (40.8%) did not carry out exclusive breastfeeding. Puerperal women who exclusively breastfed were found to have a lower risk of testing positive for PPD (10.5% vs. 13.8%, P < 0.001), in comparison to those who were not exclusively breastfeeding. After controlling for other influencing factors, exclusive breastfeeding was still associated with the lower risk of PPD (OR = 0.80, 95% CI, 0.69–0.94). Moreover, stratified analyses suggested that the association of exclusive breastfeeding with PPD was more pronounced in mothers who gave birth to a girl (P interaction < 0.05). Conclusions Our study confirms that the exclusive breastfeeding may reduce the PPD risk, especially among women with a birth of girl. Thus, more tailored preventative approaches should be developed to address PPD in women who were not exclusive breastfeeding.